Some Identities on Sums of Finite Products of Chebyshev Polynomials of the Third and Fourth Kinds - Kishore, Jugal; Verma, Vipin; Sharma, Ajay Kumar (Communications in Mathematics and Applications, 2023)
In this paper, we will introduce some identities involving sums of the finite products of Chebyshev polynomials of the third and fourth kinds, Fibonacci, and Lucas numbers in terms of the derivatives of Pell, Fibonacci, Jacobi, Gegenbauer, Vieta-Fibonacci, Vieta-Pell, and second-kind Chebyshev polynomials.